The PENGARUH KESADARAN, PENGHASILAN, SANKSI ADMINISTRATIF, DAN KUALITAS PELAYANAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PBB - P2 DI KELURAHAN WIROGUNAN KOTA YOGYAKARTA - Isfaatun, Eliya; Widy Perdana, Marsya Putri (Kajian Ekonomi dan Bisnis, 2023)
Taxpayer compliance in paying Land and Building Tax is influenced by several problems and contributing factors, namely among others taxpayer awareness, taxpayer income, administrative sanctions and quality of tax services. These factors are very realistic and attached to the daily lives of taxpayers. This study aims to test whether awareness, income, administrative sanctions and service quality affect taxpayer compliance in paying PBB – P2 in the Wirogunan sub-district, Yogyakarta City. This type of research is quantitative research. The population in this study is the obligatory PBB - P2 in the Wirogunan Village, Yogyakarta City, which amounts to 100 taxpayers. the sampling technique used is simple random sampling with the instrument used is a questionnaire. The data analysis technique uses Multiple Linear Regression Analysis and is tested with the SPSS version 25 application.The results showed that the variables of awareness, administrative sanctions, and quality of service had a partial effect on taxpayer compliance in paying PBB - P2, while the income variable had no partial effect on taxpayer compliance in paying PBB - P2. Awareness, Income, Administrative Sanctions, and Service Quality simultaneously influence taxpayer compliance in paying PBB – P2 Keywords: PBB – P2, Taxpayers, Administrative Sanctions, Service Quality, Compliance